SURVEI ATAS PEMAHAMAN SEKRETARIS DESA TERHADAP GRATIFIKASI - Septarina Prita Dania Sofianti (RELASI : JURNAL EKONOMI, 2017)
Gratuity is vulnerable from bribery and coercion infiltration. The provision of gratuity is constantly ridden by interest beyond the aspect of a personal emotional connection and social community. It’s become more complicated when gratuity transforms into a pattern of power affairs. Therefore, sekretaris desa’s and other village’s officer understanding about gratuity is very important in order to provide education to the peasant concerned gratuity. To measure their level of understanding, sekretaris desa has been surveyed and analyzed with the quantitative-descriptive   methods.   The   survey   shows   that   the   majority   of respondents do not understand about gratuity subject.